Overexpression of Galectin-7 in Mouse Epidermis Leads to Loss of Cell Junctions and Defective Skin Repair - Gendronneau, Gaëlle (PLoS One, 2015)
BACKGROUND: The proteins of the galectin family are implicated in many cellular processes, including cell interactions, polarity, intracellular trafficking, and signal transduction. In human and mouse, galectin-7 is almost exclusively expressed in stratified epithelia, notably in the epidermis. Galectin-7 expression is also altered in several human tumors of epithelial origin. This study aimed at dissecting the consequences of galectin-7 overexpression on epidermis structure and functions in vivo. METHODS: We established transgenic mice specifically overexpressing galectin-7 in the basal epidermal keratinocytes and analyzed the consequences on untreated skin and after UVB irradiation or mechanical injury. RESULTS: The intercellular cohesion of the epidermis is impaired in transgenic animals, with gaps developing between adjacent keratinocytes, associated with loss of adherens junctions. The epidermal architecture is aberrant with perturbations in the multilayered cellular organisation of the tissue, and structural defects in the basement membrane. These transgenic animals displayed a reduced re-epithelialisation potential following superficial wound, due to a defective collective migration of keratinocytes. Finally, a single mild dose of UVB induced an abnormal apoptotic response in the transgenic epidermis. CONCLUSION: These results indicate that an excess of galectin-7 leads to a destabilisation of adherens junctions associated with defects in epidermal repair. As this phenotype shares similarities with that of galectin-7 null mutant mice, we conclude that a critical level of this protein is required for maintaining proper epidermal homeostasis. This study brings new insight into the mode of action of galectins in normal and pathological situations.